(untitled) (INDIAN EDUCATIONAL REVIEW, 2025)
The Indian Educational Review is a bi-annual journal, brought out by the National Council of Educational Research and Training (NCERT), New Delhi. The journal publishes articles and researches on educational policies, practices and values material that is useful to practitioners in the contemporary times. The journal also provides a forum for teachers to share their experiences and concerns about schooling processes, curriculum, textbooks, teaching-learning and assessment practices. The views expressed by individual authors are their own and do not necessarily reflect the policies of the NCERT, or the views of the editor. ©2025*. Copyright of the articles published in the journal will vest with the NCERT and requests for reproducing the material should be addressed to the Academic Editor